Hubungan Shift Kerja dan Stres Kerja Terhadap Kepuasan Kerja Perawat di Rumah Sakit Islam Banjarmasin - Normalia Amali, Siti; Ariadi, Herman; Azhari, M. Fahrin; Amaliah, Noor (Pustaka Galeri Mandiri, 2026)
Nurses are essential healthcare providers who work in shift systems that may lead to work stress and affect job satisfaction. Poorly managed shift work can have negative impacts on nurses’ physical and psychological well-being as well as their performance. This study aimed to analyze the relationship between shift work and work stress with nurses’ job satisfaction at Islamic Hospital Banjarmasin. This study employed a quantitative design with a cross-sectional approach. The sample consisted of 60 inpatient nurses selected using stratifed random sampling. Data were collected using questionnaires and analyzed with the Spearman Rank correlation test. The results showed a significant relationship between shift work and nurses’ job satisfaction (p = 0.000; r = 0.661), and a significant relationship between work stress and job satisfaction (p = 0.000; r = 0.760). Nurses working evening and night shifts, as well as those with higher levels of work-related stress, tend to have lower job satisfaction. The study concludes that shift work and work stress are strongly related to nurses’ job satisfaction. It is recommended that hospital management implement fair shift scheduling, effective work stress management, and organizational support to improve nurses’ job satisfaction and enhance the quality of nursing care